Optimization of Two-Dimensional Ad Design with Persuasion Aspects Using Value Engineering and Analysis Hierarchy Process (Project : XYZ Singosari Car Salon) - Didik Eko Prasetyo; Fourry Handoko; Julianus Hutabarat (Jurnal Indonesia Sosial Teknologi, 2024)
XYZ Car Salon optimizes advertising to increase the company's turnover. In making advertisements requires expertise and understanding of graphic design and interesting content. Attractive design and content become the initial concern that affects customer psychology in making purchase decisions. The more attractive it is, the more effective the ad will be. This research includes a type of qualitative research, sampling using non-probability sampling methods with sampling techniques using purpose sampling, from a population of 45 experts obtained a sample of 31 respondents. The combination of design elements and persuasion elements obtained 12 advertising designs. Rankings and weights are calculated using the zero one matrix and the value matrix to get alternative design choices. The recommended choice is an A32 ad with a value of 0.85854545 costing IDR 165,000; A34 with value 0.81218182, cost Rp 110.000; A31 with a value of 0.37515789, costs Rp 95.000 and A21 with a value of 0.09916168 costs Rp 501.000.